Pelatihan Desain Kartu Nama Dan Stiker Label Nama Pada Sekolah SMA Swasta Pangeran Antasari Labuhan Deli - John, John; Rendy Prayogi; Joko Bintarto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This training aims to equip students of SMA Swasta Pangeran Antasari Helvetia Labuhan Deli with basic skills in designing and printing business cards as well as name label stickers, which they can utilize for academic purposes, organizational activities, or even small business opportunities. Additionally, this training encourages students to better understand their own potential and express it through functional visual media.In this training, the instructor uses the Canva application. The training method employed is an applicative or case study approach, starting with the introduction of the design tools to the participants before delivering the core materials. The case study method is an approach that emphasizes an in-depth analysis of a particular issue through detailed exploration.The outcome of this training provides participants with valuable skills and knowledge in utilizing easy-to-use, multi-platform design tools. These abilities will have a positive impact across various contexts, from education to entrepreneurship, and will continue to support participants in enhancing their creativity and broader design capabilities.